A review of brain oscillations in cognitive disorders and the role of neurotransmitters - Güntekin, Bahar; BAŞAR, EROL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
The analysis of the functional correlates of "brain oscillations" has become an important branch of neuroscience. Although research on the functional correlates of brain oscillation has progressed to a high level, studies on cognitive disorders are rare and mainly limited to schizophrenia patients. The present review includes the results of the changes in brain oscillations in patients with Alzheimer's, schizophrenia, bipolar disorders, mild cognitive impairment, attention-deficit hyperactivity disorder (ADHD), alcoholism and those with genetic disorders. Furthermore, the effects of pharmaca and the influence of neurotransmitters in patients with cognitive disorders are also reviewed. Following the review, a short synopsis is given related to the analysis of brain oscillations. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: brain oscillations; alpha; beta; gamma; theta; delta; schizophrenia; alzheimer; bipolar disorder; ADHD; Ach; GABA; dopamine; valproate; genetic disorders; cognitive impairment; working-memory task; human electroencephalogram eeg; multistable visual-perception; compound field potentials; hippocampal theta rhythm; auditory oddball task; necker cube reversals; gamma-band responses; alzheimers-disease; bipolar disorder; beyin salınımlar; alfa; beta; gama; teta; delta; şizofreni; alzheimer; bipolar bozukluk; dopamin; genetik bozukluklar; kognitif bozukluk; işçi bellek görevi; insan elektroensefalogram EEG; birden fazla sabit görsel-algı; bileşik alan potansiyelleri; hipokampal teta ritmi; işitsel oddball görev; necker küp ters; gama-bant tepkileri; alzheimer hastalığı